A társadalmi státusz és a választási részvétel földrajzi összefüggései Magyarországon a 2010 és 2018 közötti országgyűlési választások tükrében - Vida György; Móra Kárpát-medencei Interdiszciplináris Szakkollégiumi Konferencia (3.) (2019) (Szeged) (2021)
It is important for social justice that the principle of equal participation of citizens in elections is upheld. This is often unequal because the value of the votes is determined by where they cast their votes. In addition to the type of electoral system and the distortions of geographical delimitation, citizens' participation in the electoral process is significant. The economic and social status of the regions has a significant effect on electoral activity and its spatial dimensions also have an impact on the distribution of mandates. Therefore the examination of the geographic context of the electoral subject is the current issue. For this reason, the study examines the research question on the relationship between the economic situation and the turnout at the constituency and municipal level. With mathematical, statistical and GIS methods were used to study this topic. The results of the research provide an insight into the disparities in electoral participation at the constituency and municipal level in the light of the results of 2010, 2014 and 2018 parliamentary elections. Moreover, the investigation analyses the interrelations between turnout and socioeconomic status at a different level.
Keywords: Társadalomtudományok; Társadalom- és gazdaságföldrajz